Leucine and histidine independently regulate milk protein synthesis in bovine mammary epithelial cells via mTOR signaling pathway - Gao, Hai-na (Zhejiang University Press, 2015)

(untitled) (J Zhejiang Univ Sci B)
The aim of this study is to investigate the effects of leucine (Leu) and histidine (His) on the expression of both the mammalian target of rapamycin (mTOR) signaling pathway-related proteins and caseins in immortalized bovine mammary epithelial cells (CMEC-H), using a single supplement through Western blotting. The Earle’s balanced salt solution (EBSS) was set as the control group and other treatment groups, based on the EBSS, were added with different concentrations of Leu or His, respectively. The results showed that, compared with the control group, the expression of caseins and the phosphorylation of mTOR (Ser(2481)), Raptor (Ser(792)), eIF4E (Ser(209)), and eEF2 (Thr(56)) increased with the Leu concentrations ranging from 0.45 to 10.80 mmol/L (P<0.01). The P-4EBP1 (Thr(37)) at 10.80 mmol/L Leu, and P-RPS6 (Ser(235/236)) at 5.40 to 10.80 mmol/L Leu all decreased. Similarly, the His supplementation from 0.15 to 9.60 mmol/L increased the expression of αs2-casein, β-casein, κ-casein, P-mTOR (Ser(2481)), P-Raptor (Ser(792)), P-S6K1 (Thr(389)), P-4EBP1 (Thr(37)), P-eIF4E (Ser(209)), and P-eEF2 (Thr(56)) (P<0.01) in CMEC-H, whereas the αs1-casein expression was only reduced at 9.60 mmol/L His, G protein β subunit-like protein (GβL) at 0.15 and 9.60 mmol/L His, and P-RPS6 at 4.80 to 9.60 mmol/L His. Our linear regression model assay suggested that the αs1-casein expression was positively correlated with P-mTOR (P<0.01), P-S6K1 (P<0.01), and P-eEF2 (P<0.01) for the addition of Leu, while the expressions of β-casein (P<0.01) and κ-casein (P<0.01) were positively correlated with P-eEF2 for the addition of His. In conclusion, the milk protein synthesis was up-regulated through activation of the mTOR pathway with the addition of Leu and His in CMEC-H.